((effect of early feeding with zinc-methionine on improving growth performance and some biochemical characteristics of broilers)). Issue 1 (April 2021) - Zaki, Ali N.; Dakhel, Hashim Hadi
Abstract: This study was conducted to find out the effect of injecting hatching eggs with zinc-methionine on the hatching characteristics, production performance, and some biochemical characteristics of broilers, where 300 eggs from broiler were used, and the eggs were divided into four treatments for each treatment 75 eggs injected with zinc-methionine at concentrations (0, 60, 80 and 100 ppm) and for the treatments T1, T2, T3, and T4 respectively. From the hatched chicks, 45 chicks were taken from each treatment. They were divided into three replicates, each repeating 15 chicks. And these chicks were raised for 35 days. During the two experiments, we reached the following results: Significant superiority (P<0.05) for treatment T3 in the proportion of chicks hatching, live body weight, and total weight increase compared to the rest of the studied treatments, as there was a significant superiority (P<0.05) for the two treatments T2 and T1 in the percentage of embryo mortality compared with the rest of the studied treatments, as the results indicated a significant superiority (P<0.05) for treatment T1 in the feed consumed rate, there was a significant improvement (P<0.01) for the two treatments T4 and T3 in the feed conversion factor compared with the two treatments T2 and T1. Also, there was a significant superiority (P <0.05) for treatment T1 in the glutathione peroxidase and AST enzymes., ALT, and also manlodehydes.